2021
DOI: 10.3390/md19060325
|View full text |Cite
|
Sign up to set email alerts
|

Dermacozine N, the First Natural Linear Pentacyclic Oxazinophenazine with UV–Vis Absorption Maxima in the Near Infrared Region, along with Dermacozines O and P Isolated from the Mariana Trench Sediment Strain Dermacoccus abyssi MT 1.1T

Abstract: Three dermacozines, dermacozines N–P (1–3), were isolated from the piezotolerant Actinomycete strain Dermacoccus abyssi MT 1.1T, which was isolated from a Mariana Trench sediment in 2006. Herein, we report the elucidation of their structures using a combination of 1D/2D NMR, LC-HRESI-MSn, UV–Visible, and IR spectroscopy. Further confirmation of the structures was achieved through the analysis of data from density functional theory (DFT)–UV–Visible spectral calculations and statistical analysis such as two tail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 48 publications
(99 reference statements)
0
3
0
Order By: Relevance
“…10 Dermacozines N–P 22 , 23 , 24 , were isolated from a piezotolerant actinomycete strain Dermacoccus abyssi with dermacozine N 22 bearing a novel linear pentacyclic phenoxazine motif. 11 Genome mining of Fulvivirga sp. revealed a desferrioxamine-like BGC that contained an unknown gene fulF that is conserved in many Bacteroidetes species.…”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%
“…10 Dermacozines N–P 22 , 23 , 24 , were isolated from a piezotolerant actinomycete strain Dermacoccus abyssi with dermacozine N 22 bearing a novel linear pentacyclic phenoxazine motif. 11 Genome mining of Fulvivirga sp. revealed a desferrioxamine-like BGC that contained an unknown gene fulF that is conserved in many Bacteroidetes species.…”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%
“…In this process the electronic core phenazine structure is modified by the bacterium suggestive of compounds with differing redox properties. [2][3][4][5] To investigate this, we recorded CVs of test compounds isolated from the medium of Dermacoccus abyssi MT1.1 T (dermacozines B, E, F, O, P and phenazine-1-carboxylic acid (PCA)) in a suit-able electrolyte (0.1 M NaClO 4 in acetonitrile) [ESI S5-10 † and Table 1].…”
Section: The Dermacozine Homo-lumo Gap Energies and Dermacozine Radicalsmentioning
confidence: 99%
“…The in vivo function of these compounds is unknown, but it has been suggested that due to their range of UV-Vis absorbances, structural properties and radical scavenging activity they may participate in electron shuttling reactions. [2][3][4][5] Reports on phenazines participating in reducing matter (e.g., O 2 /O 2…”
Section: Introductionmentioning
confidence: 99%
“…[ 23 ] Dermacozine N ( 12 ), the first natural linear pentacyclic oxazinophenazinea found in nature, was obtained from a Mariana Trench sediment‐derived Dermacoccus abyssi (Figure 2). [ 24 ]…”
Section: Hot‐spot Compoundsmentioning
confidence: 99%